Balancing Challenges and Opportunities: Enhancing Early Childhood Cognitive Skills Through Digital Tools - Loka, Novita; Sabila, Rizky Thania (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
This study investigates the role of digital tools, particularly educational videos, in enhancing early childhood cognitive skills at Pertiwi Indralaya Kindergarten. Using a qualitative descriptive approach based on the Miles and Huberman framework, data were collected through classroom observations, interviews, and documentation involving 20 children aged 4–5. Findings reveal that 55% of students exhibited